Determining the voltage sag immunity of ac contactor with field testing in petrochemical plant - Hazri Dahalan, Md Razip (2021)
One of the most prominent problems in power quality is the voltage sag. It leads to equipment failure, interruptions and product damage which amount to substantial financial losses to industries. AC contactor is commonly installed in industries as a switching device due to its robust design. However, they are susceptible to voltage sag and could malfunction, leading to interruption. AC contactors were tested in the laboratory environment, which involved miniature contactors, whereas those installed in the industry are typically larger. Some of the tests referred to the SEMI F47 standard, developed specifically for the semiconductor industry. There are mixtures of ageing and new contactors in industrial operation as the former are being replaced gradually. Nevertheless, there is limited knowledge of the immunity of these contactors concerning voltage sag. A better understanding of the contactor’s immunity can assess the risk of failure, and a suitable asset management strategy can be developed. The objective of this study was to investigate the effect of voltage sag magnitude, duration and point on wave for ageing and new AC contactors installed in the industry. A field test was conducted on new and ageing contactors to produce the characteristic of voltage tolerance curves. The test setup was based on the recommendation in IEC 61000-4-11 standard. The test procedure was developed, and a test matrix was proposed to ensure efficiency and prevent error during the field test. The responses were compared to the limits recommended in IEC 61000-4-11 and SEMI F47-0706 standards. The point on wave has a significant influence on the voltage tolerance curves of the ageing contactors. On the contrary, the point on waves has an insignificant effect on the new contactors. The pattern of voltage tolerance curves does not vary when subjected to a different point on waves. Hence it is established that the new contactors are more immune to voltage sag than the ageing contactor.